USP39 regulates the cell cycle, survival, and growth of human leukemia cells. Issue 4 (5th April 2019) - Liu, Chunxia; Yao, Xiaojian; Li, Ming; Xi, Yaming; Zhao, Li
Abstract : Ubiquitin-specific peptidase 39 (USP39) is one member of the cysteine proteases of the USP family, which represents the largest group of DeUbiquitinases with more than 50 members in humans. The roles of USP39 in human cancer have been widely investigated. However, the roles of USP39 in human leukemia and the underlying mechanism remain unknown. Here we reported the function of USP39 in human leukemia. We observed that the expression of USP39 was up-regulated in human leukemia cells and the high expression of USP39 was correlated with poor survival of the patients with leukemia. Lentivirus-mediated knockdown of USP39 repressed the proliferation and colony formation of human leukemia cell lines HL-60 and Jurkat cells. Mechanism study showed that USP39 knockdown induced the arrest of cell cycle and apoptosis of leukemia cells. In addition, our microarray and bioinformatic analysis demonstrated that USP39 regulated diverse cellular signaling pathways that were involved in tumor biology, and several pivotal genes ( IRF1, Caspase 8, and SP1 ) have been validated by quantitative real-time polymerase chain reaction. Knockdown or IRF1 partially restored the proliferation rate of leukemia cells with USP39 knockdown. Taken together, our findings implicate that USP39 promotes the development of human leukemia by regulating cell cycle, survival, and proliferation of the cells.